Customer satisfaction acts as a mediator variable in the relationship between customer citizenship behavior and the halal label, pricing, and product quality - Salsabila Nadira; Abror Abror (Marketing Management Studies, 2023)
This study aims to analyze how the influence of the halal label, price and product quality on customer citizenship behavior with Customer satisfaction as a mediating variable for Wardah Cosmetics customers in Padang City. This research was conducted using a quantitative method. The population in this study are Wardah Cosmetic customers in the city Padang who is Muslim and bought Wardah products in the last 6 months. The research sample is 374 respondents. This study uses a structural equation model (SEM) test with smart PLS software as a data analysis tool. The results of this study found that: (1) Halal Label has a positive influence on Customer Satisfaction. (2) Price has a positive influence on Customer Satisfaction. (3) Product quality has a positive influence on Customer Satisfaction. (4) Product Quality has a positive influence on Price. (5) Customer Satisfaction has a positive influence on Customer Citizenship Behavior